The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.jpclett.0c00581
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Material Composition Effects on the Gamma Ray Stability of Lead Halide Perovskite Solar Cells: MAPbI3 Breaks the Records

Abstract: In this work, we report a comparative study of the gamma ray stability of perovskite solar cells based on a series of perovskite absorbers including MAPbI 3 (MA = methylammonium), MAPbBr 3 , Cs 0.15 FA 0.85 PbI 3 (FA = formamidinim), Cs 0.1 MA 0.15 FA 0.75 PbI 3 , CsPbI 3 , and CsPbBr 3. We reveal that the composition of the perovskite material strongly affects the radiation stability of the solar cells. In particular, solar cells based on the MAPbI 3 were found to be the most resistant to gamma rays since thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…On the contrary, the MAFA-Mix and CsFA-Mix samples show a decrease in the amount of Pb 0 during irradiation, not an increase, suggesting a reaction that consumes Pb 0 faster than it is formed. A similar process allowed encapsulated MAPbI 3 to reform after decomposition under gamma radiation as proposed by Boldyreva et al 15 The new nitrogen species observed during radiolysis of the organic cation are very likely, in part, responsible for this self-healing process. Radiolysis of ammonium halide salts and alkylammoium halide salts has been shown to result in the production of halide containing radicals.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…On the contrary, the MAFA-Mix and CsFA-Mix samples show a decrease in the amount of Pb 0 during irradiation, not an increase, suggesting a reaction that consumes Pb 0 faster than it is formed. A similar process allowed encapsulated MAPbI 3 to reform after decomposition under gamma radiation as proposed by Boldyreva et al 15 The new nitrogen species observed during radiolysis of the organic cation are very likely, in part, responsible for this self-healing process. Radiolysis of ammonium halide salts and alkylammoium halide salts has been shown to result in the production of halide containing radicals.…”
Section: Resultsmentioning
confidence: 56%
“…damage) is required to initiate the degradation, which in turn appears to catalyse further degradation, meaning that degradation could be limited or avoided by reducing the X-ray fluence. Additionally, at 3.2x10 15 photons/s/cm 2 the formation of metallic lead is significantly slower than at higher intensities, indicating that the reaction behaves differently at lower X-ray flux densities. Therefore, the same total fluence can give less damage at lower X-ray flux densities suggesting that the X-ray stability is improved by limiting the maximum X-ray flux density.…”
Section: X-ray Stability and Degradation Of The Inorganic Cspbbrmentioning
confidence: 95%
See 3 more Smart Citations